2007
DOI: 10.1007/s10562-007-9283-6
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversions of Polychlorinated Benzenes and Dioxins with Low-chlorine Using V2O5/TiO2

Abstract: Chlorinated benzene, especially 1,2-dichlorobenzene (1,2-DCB), has been widely used as one of surrogate compounds of dioxin to find the noble methods to control dioxin. However, the relationship between the catalytic activity of dioxin surrogate compound and dioxin has not been understood quite well. In this work, we used a vanadium based catalyst (V 2 O 5 /TiO 2 ) to compare catalytic activity of chlorinated benzenes and dibenzo-p-dioxins with low-chlorine content using the lab-scale system. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the previous experimental research studies, PCDD/Fs are often replaced by model compounds, such as chlorobenzenes 4,9,15 and chlorophenols, 16,17 which are less toxic and more convenient for detection. However, as reported in several studies, [18][19][20] the catalytic performance and mechanism for these model compounds may not be consistent with those for PCDD/Fs due to the significant differences between their chemical structures. Furthermore, some important intermediates that formed during the process of the reactions might be too transient to be discernible by the experimental studies.…”
Section: Introductionmentioning
confidence: 78%
“…In the previous experimental research studies, PCDD/Fs are often replaced by model compounds, such as chlorobenzenes 4,9,15 and chlorophenols, 16,17 which are less toxic and more convenient for detection. However, as reported in several studies, [18][19][20] the catalytic performance and mechanism for these model compounds may not be consistent with those for PCDD/Fs due to the significant differences between their chemical structures. Furthermore, some important intermediates that formed during the process of the reactions might be too transient to be discernible by the experimental studies.…”
Section: Introductionmentioning
confidence: 78%
“…Since HCBz is a perfect surrogate of PCDD/Fs, PCBs, and PeCBz in catalytic destruction reaction, , BM synthesized MnO x with excellent HCBz removal performance is potentially effective for the destruction of other POPs. More over, the facile scalable catalyst production facilitates the construction of catalyst module.…”
Section: Resultsmentioning
confidence: 99%
“…S3). HCBz was adopted as a surrogate of UPOPs [37]. It can be observed that the fabrication of Fe 3 O 4 on OL lowered the catalytic activity, probably due to the partially coverage of reactive surface.…”
Section: Upops Removal Activitymentioning
confidence: 99%